Prevalence and risk factors of Helicobacter pylori infection in Xinjiang Uygur Autonomous Region: A cross-sectional study of all age groups - Jiang, Qi; Liu, Wei-Dong; Hui, Wen-Jia; Kong, Wen-Jie; Feng, Yan; Kuerbanjiang, Aihemaijiang; Huang, Xiao Ling; Gao, Feng (World journal of gastroenterology : WJG, 2025)
BACKGROUND Helicobacter pylori (H. pylori) infection rates have been changing with different populations and geographic areas. Currently, there is still a lack of comprehensive survey data on the H. pylori infection rate and its risk factors in the natural population of Xinjiang Uygur Autonomous Region. AIM To understand the H. pylori infection and risk factors in Xinjiang Uygur Autonomous Region for the prevention and control strategies METHODS This study comprehensively collected the survey data on H. pylori infection in 15 regions of Xinjiang Uygur Autonomous Region by using the method of stratified random cluster sampling. A total of 4361 individuals from the general population were selected as research subjects, and questionnaire surveys and blood tests for H. pylori antibodies were conducted. RESULTS The overall H. pylori infection rate in Xinjiang Uygur Autonomous Region was 70.79% (3087/4361). The H. pylori infection rate showed a trend of first increasing and then decreasing with the increase of age, and the difference was statistically significant (P < 0.05). The analysis of the H. pylori infection rates among different ethnic groups showed that the infection rates of ethnic minorities such as Uyghur, Kirgiz, and Tajik were significantly higher than those of Han and Hui ethnic groups, and the difference was statistically significant (P < 0.01). Multivariate analysis showed that altitude, regular consumption of beef, mutton, dried nuts, barbecue foods, and drinking river water were positively correlated with the H. pylori infection rate. CONCLUSION This study indicates that the overall H. pylori infection rate in Xinjiang Uygur Autonomous Region is relatively high, with obvious regional and ethnic differences, which are closely related to the sanitation conditions and eating habits.